Scientific production on the use of artificial intelligence in higher education in Latin America - Mieles-Briones, Wilmer; Moreira-Mieles, Liggia Lisbeth; Quidemil-Torrijo, Eneida Maria; Molina-Arteaga, Karol Denisse (Revista General de Información y Documentación, 2025)
In the coming years, artificial intelligence (AI) is estimated to play a decisive role in the educational field in the transformation of teaching and learning methods. This research aims to analyze the scientific production on the use of AI in the context of higher education according to Scopus in the period 2019-2023. A bibliometric study of relevant literature was carried out with the aim of presenting an updated view of knowledge in a specific area or topic, where indicators of productivity, thematic co-occurrence, and impact were analyzed. In general terms, the topics covered in these studies indicate that research on the use of AI and emerging technologies in education is growing rapidly, where specialized journals and various authors have consolidated collaboration networks in a rapidly expanding field. Mexico leads scientific production in Latin America.